The governance structure on the role of internal auditors in environmental auditing practices: Cases of Malaysian local organisations - Muthyaah Mohd Jamil; Nor Hafizah Zainal Abidin; Norhayati Mohd Alwi (Environmental Challenges, 2022)
This study investigates how governance structures’ internal auditors play their roles in environmental auditing practices. This study used interpretative research focusing on multiple case studies: two Malaysian Local Governments with single-case design and environmental auditing. This study utilised three methods of data collection: document analysis, observations and interviews. This study used thematic analysis using Atlas.Ti software. This study concludes that governance structures such as NGO Watchdog Group, independence of the internal audit department, tenure of Chairman, multiple functions and review meetings influence the roles of the internal audit department. This study explores the environmental auditing practices using expectation development by Role Theory to illustrate the process of environmental auditing practices. The findings outline how to construct environmental auditing practices and improve the effectiveness of the practices in government organisations.